Development of a Customer Satisfaction Model for Mobile Banking Usage through a Gender Moderation Approach at HIMBARA Banks in East Java - Endie Rianto; Slamet Riyadi; Sri Utami Ady (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Mobile banking services have become the primary channel for banking transactions in Indonesia, with HIMBARA Bank active users reaching 79.75 million in 2024. However, customer satisfaction levels remain variable, and the role of gender as a moderating factor has not been extensively studied. Method: This study employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Moderated Regression Analysis (MRA). Data were collected from 371 mobile banking users of HIMBARA Banks (Bank Mandiri, BRI, BNI, BTN) in five major cities in East Java. The independent variables consist of technology (X1), knowledge (X2), trust (X3), security (X4), and risk (X5), with usage decision (Z) as the intervening variable, gender (M) as the moderating variable, and customer satisfaction (Y) as the dependent variable. Results: Technology (β=0.175; p=0.001) and knowledge (β=0.231; p=0.000) had a significant positive effect on customer satisfaction. Risk had a negative yet non-significant effect on satisfaction (β=−0.029; p=0.599). Trust (β=0.047; p=0.405) and security (β=0.114; p=0.067) were not found to have a significant direct effect on satisfaction. The mobile banking usage decision was proven to mediate the effects of technology, trust, security, and risk on customer satisfaction. Gender did not significantly moderate the relationship between usage decision and satisfaction (β=0.020; p=0.597). The R² value of customer satisfaction was 0.513. Conclusion: The developed model confirms that technology and knowledge are the primary determinants of customer satisfaction among mobile banking users, while the usage decision plays an important role as a mediator. The key distinction from the original dissertation lies in the reduction of independent variables to five (removing rapid service and ease of use), yielding a more parsimonious model focused on intrinsic factors of digital banking technology adoption